The Urgency of Community Legal Awareness in Traffic in Southern Tapanuli - Hsb, Putra Halomoan; Harahap, Nasruddin Khalil (Studi Multidisipliner: Jurnal Kajian Keislaman, 2024)
This research seeks to see the legal awareness of the community in carrying out traffic in the Southern part of Tapanuli by not being followed by coercion without pressure, or orders from outside to obey the applicable law. As legal awareness progresses in the community, the law does not need to impose sanctions. The purpose of this research is to find out the level of legal awareness of the community in traffic on the road. knowing the obstacles of the community in understanding the legal awareness of the community in traffic on the road and knowing the efforts made by law enforcement to overcome the low level of legal awareness of the community in traffic on the road in the southern part of Tapanuli. The method in this research is by using a qualitative research method by interviewing several sources and conducting mini research related to the title raised in the study. Results: This study increases knowledge and understanding for the author, especially regarding the issues researched related to traffic law awareness on the road. Conclusion: The public's legal awareness in traffic is very minimal, even though law enforcement against motor vehicle violations on the road has been regulated in Law Number 22 of 2009 concerning Road Traffic and Transportation.